MODEL PENGEMBANGAN KURIKULUM TPQ AL FURQON MTA WONOSARI 1 - Ummu Hani’; Istanto Istanto (UIN Sumatera Utara Medan, 2025)
This study aims to examine the curriculum model, curriculum development, and the supporting and inhibiting factors of curriculum development in TPQ Al Furqon MTA Wonosari 1. The method used is phenomenology with a qualitative data analysis approach. Data were collected through observation and interviews, then analyzed descriptively through the process of transcription, coding, categorization, description, and interpretation. The instrument used in this research was an interview sheet submitted to the Head of TPQ Al Furqon MTA Wonosari 1 to obtain valid data. The results of this study reveal that TPQ Al Furqon MTA Wonosari 1 uses a curriculum model compiled by the LPQ MTA Center, whose material is based on MTA teachings that refer to the Al-Qur'an and As-Sunnah, and is adapted to the conditions that exist at TPQ Al Furqon MTA Wonosari 1. TPQ Al Furqon MTA Wonosari 1 has developed by continuing to innovate in learning, such as the use of the classical Iqra' method for efficiency. In TPQ learning is focused on achieving key competencies such as reading, writing, memorizing the Qur'an, understanding worship, and morals.